ANALISIS PERBANDINGAN PENGUKURAN RISIKO PASAR STANDARDIZED MODEL DAN INTERNAL MODEL PADA SURAT UTANG NEGARA PORTOFOLIO TRADING (STUDI KASUS BANK XYZ) - , Dhevy Hardanta; , Prof. Dr. Sukmawati Sukamulja, M.M. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This thesis analyzes the market risk measurement at Bank XYZ for Government Securities portfolio. The method used is the Standardized Model and Internal Models, Value at Risk (VaR). The use of such models as the consideration for the banking industry in particular provision of capital charges set-off between income and the provision of risk when a bank hold Government securities Portfolio Trading. The purpose of this study compared the provision of risk both models of Capital Charges. The results concluded that the Internal Model approach (VaR) is more accurate and provide better levels of effectiveness of capital allocation than the Standardized Model approach.Using Internal Model will reduce capital charges.